2008
DOI: 10.2136/sssaj2007.0078
|View full text |Cite
|
Sign up to set email alerts
|

XANES Speciation of Phosphorus in Organically Amended and Fertilized Vertisol and Mollisol

Abstract: Knowledge of the dominant P species present in the soil following the application of organic amendments and fertilizer is important in understanding the fate of P in the environment. This study was performed to identify P species in two calcareous soils, an Osborne series (Typic Humicryert) and a Lakeland series (Typic Calciudoll), treated with organic amendments (biosolids and hog and dairy cattle manure) and fertilizer (monoammonium phosphate, MAP). Phosphorus 1s x‐ray absorption near‐edge structure (XANES) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 21 publications
3
57
0
1
Order By: Relevance
“…However, XANES LCF analysis did not reveal any P o species in either investigated colloidal sample (Fig. 1), probably because they were below the detection limit of XANES spectroscopy or due to a lack of distinctive spectral features of P o compounds (Beauchemin et al, 2003;Ajiboye et al, 2008;Kruse and Leinweber, 2008). As such, analysis with solution P-NMR was required to provide molecular speciation information about the P pool colorimetrically classified as MUP.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, XANES LCF analysis did not reveal any P o species in either investigated colloidal sample (Fig. 1), probably because they were below the detection limit of XANES spectroscopy or due to a lack of distinctive spectral features of P o compounds (Beauchemin et al, 2003;Ajiboye et al, 2008;Kruse and Leinweber, 2008). As such, analysis with solution P-NMR was required to provide molecular speciation information about the P pool colorimetrically classified as MUP.…”
Section: Resultsmentioning
confidence: 95%
“…Synchrotron-based P K-edge XANES spectroscopy provides an extraordinarily valuable method to investigate the solid-phase species of P in heterogeneous samples such as soils (Ajiboye et al, 2008;Beauchemin et al, 2003;Kizewski et al, 2011), sediments (Giguet-Covex et al, 2013), and wastes (Toor et al, 2006). This technique is a nondestructive molecular probe for P speciation and is especially efficient for inorganic P (P i ) forms with unique spectral fingerprints.…”
Section: Molecular Speciation Of Phosphorus Present In Readily Dispermentioning
confidence: 99%
“…An earlier and more detailed study by Beauchemin et al (2003) using adsorbed P and mineral P standards confirmed that hydroxyapatite and octocalcium phosphate can indeed be identified in soils. In their soils, these two compounds comprised up to 85% of the total P. Hence, despite some reports asserting that P precipitation is not an important process in controlling P availability and hence fertiliser efficiency (Syers et al 2008), recent direct spectroscopic evidence suggests the opposite (Beauchemin et al 2003;Lombi et al 2006;Ajiboye et al 2008). …”
Section: Precipitation Of Soluble Phosphorusmentioning
confidence: 94%
“…In addition, both the manure and compost contained Fe, which could form Fe phosphates, thereby reducing P solubility. Ajiboye et al (2008) found that calcareous soils amended with dairy manure had significant amounts of strengite (FePO 4 ) formation, whereas these same soils treated with MAP did not.…”
Section: Leytem Et Almentioning
confidence: 99%